2020
DOI: 10.1186/s12931-020-01579-7
|View full text |Cite
|
Sign up to set email alerts
|

A cluster-based analysis evaluating the impact of comorbidities in fibrotic interstitial lung disease

Abstract: Background Comorbidities are frequent and have been associated with poor quality of life, increased hospitalizations, and mortality in patients with interstitial lung disease (ILD). However, it is unclear how comorbidities lead to these negative outcomes and whether they could influence ILD disease progression. The goal of this study was to identify clusters of patients based on similar comorbidity profiles and to determine whether these clusters were associated with rate of lung function decline and/or mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 26 publications
6
19
1
Order By: Relevance
“…Age has been identified as a risk factor for ILD progression [ 35 ]. Furthermore, older age is particularly known in to increase the likelihood of progression and mortality in progressive fibrosing phenotypes [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Age has been identified as a risk factor for ILD progression [ 35 ]. Furthermore, older age is particularly known in to increase the likelihood of progression and mortality in progressive fibrosing phenotypes [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…We considered the baseline covariates age (in years), sex, duration of disease (in years), smoking status (current or former and never-smoker), study center, comorbidity burden and physician-reported information on forced vital capacity (FVC) % predicted. In addition, we considered four different ILD subtypes: (1) Sarcoidosis, (2) IPF, (3) PF-ILD (determined by a decrease of at least 10% in either FVC %predicted or DLCO %predicted values after 12 months [ 12 ]), as well as (4) other ILD subtypes. Other ILD subtypes comprised of idiopathic interstitial pneumonias, hypersensitivity pneumonitis, rheumatic and connective tissue diseases with pulmonary involvement, drug-related ILD, combined pulmonary fibrosis and emphysema, non-classifiable ILD and other forms.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations